Satisfacción de los usuarios del servicio de agua potable que brinda EPS Sedaloreto Sociedad Anónima, Iquitos mayo 2022 - Fernandez Perez, Alex Wilhem (2023)
The research work satisfaction of the users of the water service provided by EPS SEDALORETO Sociedad Anónima, Iquitos May 2022, its main objective is to determine the degree of customer satisfaction with the drinking water service provided by EPS SEDALORETO S.A. The study was descriptive, simple, non-experimental and cross-sectional, and it was carried out in May 2022 in the metropolitan area of Iquitos. The population is 62,136 users and 382 users from each of the four districts —Punchana, Iquitos, Belén and San Juan Bautista— make up the stratified sample. The results show that 75.10% of the users have an average satisfaction. 13.40% stated that they have low satisfaction and 11.50% of the total users of metropolitan Iquitos stated that they have high satisfaction with the drinking water services provided by EPS SEDALORETO as of May 2022.